Morfometria do relevo e dinâmica erosiva linear em área rural degradada no Oeste Paulista - Zanatta, Felipe Augusto Scudeller [UNESP]; Lupinacci, Cenira Maria [UNESP]; Boin, Marcos Norberto (Universidade Federal do Paraná, 2017)
In the southeastern region of Brazil, one of the main soil degradation factors is related to linear erosion, as a consequence of intense deforestation. Considering this problem, this article aimed to evaluate the spatial correlation of relief morphometry with linear erosive features, in order to better understand the dynamics of such processes in a watershed located in Marabá Paulista town (SP). To do so, the erosive features in rill erosion, gully and badlands, in the scenarios of 1963, 1997 and 2015, and the relief morphometry were mapped on a scale 1: 10, 000. Through mappings, the area affected by grooves, ravines and gullies of all scenarios and the area occupied by each relief morphometry class were quantified. These data were later evaluated through the Pearson Correlation Coefficient (p) and the normalized density. As a result, in the studied watershed, which since 1963 has presented more than 90% of the surface cover altered for agropastoral purposes, the erosive process was observed to progressively and systemically evolve throughout the scenarios. The expansion of the area reached by badlands generated the advance of the gully's to sectors whose morphometry, theoretically, does not provide conditions for the occurrence of such processes. The same phenomenon occurs with the rill erosion, which, due to regressive erosive action, are positioned at the tops, with low morphometric potentiality. It was also observed that, despite the use of several erosion control techniques, these did not contribute to the resolution of the problem.
Relief morphometry and linear erosive dynamics in degraded rural area in West Paulista
Keywords: Deforestation; Linear erosive features; Soil degradation